On‐call pharmacist enquiries and outcomes: an on‐call database review, 2003–2012. (December 2014) - Heath, Emily K.; Welch, Susan A.; Costello, Nicholas
Abstract: Aim: To describe enquiries to an after‐hours on‐call pharmacist service (2003–2012) and outcomes documented in Clinical Pharmacy Meeting (CPM) minutes (2012). Methods: Data entered by on‐call pharmacists into the Access database at a tertiary referral hospital were retrospectively reviewed. Data were analysed using Excel. CPM minutes were reviewed to determine outcomes. Results: 'Drug‐based' enquiries (94%, 909/963) and 'non‐drug‐based' enquiries (6%, 54/963) were received. The majority were answered from home (74%, 711/963), while 26% (252/963) required the pharmacist to return to the pharmacy. Most calls occurred between 17:00 and 08:00 (59%, 569/963), with a peak period between 18:00 and 22:00 (41%, 393/963). The most common 'drug‐based' enquiries were drug availability (54%, 540/909) and drug information (26%, 235/909). Overall, enquiries involved 372 different drugs, 13% (47/372) being involved in five or more enquiries and 64% (30/47) of these could be classified by 'A PINCH' High Risk Classification, notably anti‐infectives (40%, 12/30). 'Non‐drug‐based' enquiries involved issues with logistics of discharge medications, refrigerators, security alarms, and 32% (17/54) required the pharmacist to return to the pharmacy. On‐call enquiries during pharmacy opening hours before and after implementation of a Sunday service (2011) reduced. Documented outcomes of enquiry review in CPM minutes included: review of medication protocols, additions to the after‐hours drug cupboard and provision of education. Conclusion: A review of the on‐call pharmacist enquiries supported the provision of the service as they commonly involved high‐risk 'A PINCH' medications and were from acute areas. These medications and the acute areas warrant timely and additional pharmacist input in order to ensure patient safety. The service demonstrates efficiency through management of enquiries from home and positive outcomes resulting from regular review at meetings.